Integration of Personal Safety in Students Training on the Specialty “Civil Safety” at Technical Institutions of Higher Education - Yevtushenko, Nataliіa; Tverdokhliebova, Natalia (Educational Challenges, 2024)
Security is considered a legitimate goal of every society. In recent years of the pandemic and then the war in Ukraine, the issue of the security paradigm has become particularly relevant. It prompts a revision of conceptual approaches to the formation of human personal security competencies and especially the mechanisms and ways of ensuring it in society and the state in the present conditions. Therefore, in theory, national and international security concepts are being developed, and more recently, individual, social, and global security. This indicates, among other things, a significant expansion of new dimensions of security when political independence, territorial integrity, and viability of the country, as well as the survival and development of its inhabitants, are at stake. Security in itself should have the status of a fundamental human right. Many publicly discussed security issues are related to technical solutions. Debates are underway not only about society's attitude to security, but also about what research and for what purpose it is conducting or has conducted in this direction. This also applies to the educational environment. The article defines and substantiates the principles of the formation of personal safety of students, provides an essential characteristic of the pedagogical process of formation of personal safety of students, considers the technology of formation of personal safety of students based on the competence approach, reveals the content of the competences of the individual in the sphere of life safety. The purpose of this article is to study the process of forming the personal safety of students in the system of professional education in higher technical institutions of a technical profile. The methodology on which the research is grounded is based on the methodological principles of systematicity and an interdisciplinary approach and includes the use of a complex of general scientific methods, namely explanation, comparison, classification, generalization, and systematization. Based on them, a model of forming students' competencies in the life safety field was built. Within the framework of our research, the following results were achieved: the views of scientists on the issue of the formation of security competencies among students in the new context of the construction of Ukrainian society in conditions of war were summarized; the principles of forming students' personal safety based on the competence approach are substantiated; tasks for the development of students' competencies in the field of life safety are formulated; a structural model of students' competencies and the process of their formation in the field of life safety was built. The conclusions allow us to state that the problem of security is complex and multifaceted, since conflicts, wars or unstable state structures often have not only local significance, but also global consequences due to a closely interconnected and globalized world. The formation of personal safety competencies in students as future specialists is important as a basis for self-preservation, self-development and self-improvement. For this purpose, educational professional programs of technical universities should include fundamental educational disciplines that will ensure the development of worldview principles of life safety and determine generally accepted safety needs and generally recognized safety mechanisms.